Analisis Postur Kerja Dengan Rapid Entire Body Assessment (REBA) Untuk Mengurangi Risiko Musculoskeletal Disorders - Berty Dwi Rahmawati; Eka Anggraini (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
PT SC is engaged in the cement industry. One of the parts in PT SC is the packing plant, in which there are various activities such as lifting and arranging sack cement on trucks. The lifting and arrangement of the sack cement is carried out manually by the worker in a bent body position and added with a load of cement that must be lifted, namely 50 kg, this position is carried out repeatedly with a working duration of less than 12 hours. The REBA (Rapid Entire Body Assessment) method will be used to analyze the work posture of workers. This method is used to analyze body posture which is used to analyze all parts of the body. Work posture assessment was carried out on four workers with conditions before and after sacking cement removal. Based on the measurement results, the average score obtained is +10 which means it has a high risk so that investigation and implementation of changes are needed.